Забезпечення дотримання обмежень під час проходження публічної служби в розбудові інституту публічної служби України - Шовкун, Ю. І.; Shovkun, Yu. I. (Право і суспільство. - 2023. - № 4. - С. 242-248, 2023)
Окреслено значення забезпечення дотримання обмежень під час проходження публічної служби в розбудові інституту публічної служби України. Проведено диференціацію вказаних обмежень і визначено роль кожного з них. Зроблено висновок про значення забезпечення дотримання обмежень під час проходження публічної служби, яке полягає у наступних проявах: 1) вони мають антикорупційну спрямованість, превентивної дії, оскільки їх встановлення призводить до попередження вчинення корупційних і пов’язаних із корупцією правопорушень; 2) сприяють утвердженню національної безпеки; 3) зміцнюють інститут публічної служби; 4) гарантують об’єктивну реалізацію принципу законності, зокрема за рахунок доброчесності публічних службовців.

The article emphasizes the need to approve certain requirements and rules: selection of candidates for the positions of public servants; completion of public service, as well as the establishment of restrictions in order to establish integrity in professional activity and reduce the level of offenses. The purpose of the article is to outline the importance of ensuring compliance with restrictions during public service. The latter are divided into three groups: 1)restrictions placed on candidates for public service positions; 2) restrictions are stipulated by anti-corruption legislation; 3) restrictions are provided by the rules of professional ethics. It is noted that compliance with the requirements and restrictions imposed on candidates for public service positions is important not only from the point of view of professionalism, but also from the point of view of national security. Ensuring anti-corruption restrictions have a double meaning, since on the one hand they are used as a tool for the prevention and prevention of administrative offenses related to corruption, which positively affects the level of legality of actions of public officials and their integrity, and on the other hand – reduces the level of corruption in the sphere of public administration services that eliminate the possibility of its destabilization. The establishment of restrictions provided for by the rules of professional ethics is carried out to ensure two main points: first, the honest and qualified performance of the duties assigned to them by public servants; secondly, warning and preventing the desire of a public servant to change the vector of his own interests from public to private, including to the detriment of the interests of states and society. A conclusion was made about the importance of ensuring compliance with restrictions during public service, which consists in the following manifestations: 1) they have an anti-corruption orientation, preventive action, since their establishment leads to the prevention of the commission of corruption and corruption-related offenses; 2) contribute to the establishment of national security; 3) strengthen the institution of public service; 4) guarantee the objective implementation of the principle of legality, in particular at the expense of the integrity of public officials.

Обозначено обеспечение соблюдения ограничений во время прохождения публичной службы в развитии института публичной службы Украины. Проведена дифференциация указанных ограничений и определена роль каждого из них.
Ensuring compliance with restrictions during public service in the development of the public service institute of Ukraine
Keywords: публічна служба; public service; публичная служба; державна служба; обмеження; limitation; ограничение; антикорупційні обмеження; anti-corruption restrictions; антикоррупционные ограничения; морально-етичні правила; moral and ethical rules; морально-нравственные правила; національна безпека; national security; национальная безопасность